The Impact of Reimbursement for Non–Face-to-Face Chronic Care Management on Comprehensive Metabolic Biomarkers Among Multimorbid Patients With Type 2 Diabetes. Issue 3 (10th March 2023) - Shao, Yixue; Stoecker, Charles; Hong, Dongzhe; Nauman, Elizabeth; Fonseca, Vivian; Hu, Gang; Bazzano, Alessandra N.; Fort, Daniel; Kabagambe, Edmond K.; Shi, Lizheng
Abstract : Aims: We evaluated the impact of reimbursement for non–face-to-face chronic care management (NFFCCM) on comprehensive metabolic risk factors among multimorbid Medicare beneficiaries with type 2 diabetes in Louisiana. Materials and Methods: We implemented a propensity score method to obtain comparable treatment (n=1501 with NFFCCM) and control (n=17, 524 without NFFCCM) groups. Patients with type 2 diabetes were extracted from the electronic health records stored in REACHnet. The study period was from 2013 to February 2020. The comprehensive metabolic risk factors included the primary outcome of glycated hemoglobin (HbA1c) (as the primary outcome) and the secondary outcomes of body mass index (BMI), systolic blood pressure (BP), and low-density lipoprotein cholesterol. Results: Receiving any NFFCCM was associated with improvement in all outcomes measures: a reduction in HbA1c of 0.063% (95% CI: 0.031%–0.094%; P <0.001), a reduction in BMI of 0.155 kg/m 2 (95% CI: 0.029–0.282 kg/m 2 ; P =0.016), a reduction in systolic BP of 0.816 mm Hg (95% CI: 0.469–1.163 mm Hg; P <0.001), and a reduction in low-density lipoprotein cholesterol of 1.779 mg/dL (95% CI: 0.988 2.570 mg/dL; P <0.001). Compared with the control group, the treatment group had 1.6% more patients with HbA1c <7% (95% CI: 0.3%–2.9%; P =0.013). Conclusions: Patients with diabetes in Louisiana receiving NFFCCM experienced better control of HbA1c, BMI, BP, and low-density lipoprotein outcomes.